2015
DOI: 10.1016/j.ajhg.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in DDX58, which Encodes RIG-I, Cause Atypical Singleton-Merten Syndrome

Abstract: Singleton-Merten syndrome (SMS) is an autosomal-dominant multi-system disorder characterized by dental dysplasia, aortic calcification, skeletal abnormalities, glaucoma, psoriasis, and other conditions. Despite an apparent autosomal-dominant pattern of inheritance, the genetic background of SMS and information about its phenotypic heterogeneity remain unknown. Recently, we found a family affected by glaucoma, aortic calcification, and skeletal abnormalities. Unlike subjects with classic SMS, affected individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
173
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(181 citation statements)
references
References 22 publications
7
173
0
1
Order By: Relevance
“…In addition, patients may suffer from psoriasis, early-onset glaucoma and recurrent infections. Singleton-Merton syndrome is inherited in an autosomal dominant manner and caused by heterozygous mutations in IFIH1 (SGMRT1; OMIM 182250) or RIGI (SGMRT2; OMIM 616298) encoding cytosolic pattern recognition receptors for dsRNA [74,75]. Functional studies have shown that IFIH1 or RIGI mutations in patients act as gain-offunction mutations which results in constitutive type IFN activation.…”
Section: Singleton-merten Syndromementioning
confidence: 98%
“…In addition, patients may suffer from psoriasis, early-onset glaucoma and recurrent infections. Singleton-Merton syndrome is inherited in an autosomal dominant manner and caused by heterozygous mutations in IFIH1 (SGMRT1; OMIM 182250) or RIGI (SGMRT2; OMIM 616298) encoding cytosolic pattern recognition receptors for dsRNA [74,75]. Functional studies have shown that IFIH1 or RIGI mutations in patients act as gain-offunction mutations which results in constitutive type IFN activation.…”
Section: Singleton-merten Syndromementioning
confidence: 98%
“…Mutations in DDX58 encoding RIG-I, have recently been described in 11 patients from 2 families with glaucoma and skeletal abnormalities [12]*. The musculoskeletal manifestations include arthritis of hands and feet, joint contractures, calcific tendinitis, and, erosive changes in the terminal tufts of the distal phalanges.…”
Section: Introductionmentioning
confidence: 99%
“…The musculoskeletal manifestations include arthritis of hands and feet, joint contractures, calcific tendinitis, and, erosive changes in the terminal tufts of the distal phalanges. Four patients had aortic and valvular calcification; psoriasiform rashes were present in 8 individuals and most patients had glaucoma [12]*. Transfection of wildtype and mutant DDX58 into HEK293T cells showed increased basal reporter gene activity of NF-κB and of the IFNB1 enhancer region PRDIII-I [12]*.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency of components of the immunoproteasome (PSMB8, PSMA3, PSMB4, PSMB9, POMP) causes chronic type I IFN activation by yet unknown mechanisms that may involve antigen presentation. AGS Aicardi-Goutières syndrome, RVCL retinal vasculopathy with cerebral leukodystrophy, CHBL familial chilblain lupus, XLPDR X-linked reticulate pigmentary disorder, SAVI STING-associated vasculopathy, infantile-onset, SGMRT SingletonMerton syndrome, SPENCD spondyloenchrondrodysplasia, CANDLE chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature SGMRT2), AGS and STING-associated vasculopathy (SAVI), respectively [20][21][22][23]. Finally, dysregulation of pathways that modulate type I IFN signaling can cause ISG15 or USP18 deficiency, spondyloenchondrodysplasia, or CANDLE syndrome [10,[24][25][26].…”
mentioning
confidence: 99%